Upaya Guru dalam Meningkatkan Kemampuan Literasi Siswa di UPT SDN Talang Tangah: Studi Kualitatif - Nurul Azizah; Rangga Syaputra; Safrizal Safrizal; Sunarti Sunarti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This research is motivated by the low literacy skills of students in Indonesia and the less than optimal reading culture at the UPT SDN Talang Tangah. The purpose of this study is to analyze teachers' efforts in improving students' reading literacy skills at the school. This study uses a qualitative approach with a case study research type. Researchers collected data through in-depth interviews, observations, and documentation with purposive sampling techniques. Data analysis using the Miles and Huberment model consisting of data reduction, data display and conclusions. carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that teachers implemented various creative strategies, including reading habits at the beginning of learning, retelling activities, word play methods (learning through play), and the use of concrete media such as cards and letter boards. This strategy has proven effective in creating a fun learning atmosphere while increasing student understanding and involvement in literacy activities in elementary schools.